2007
DOI: 10.1107/s1600536807017345
|View full text |Cite
|
Sign up to set email alerts
|

N,N′-Bis[4-(trifluoromethyl)benzylidene]butane-1,4-diamine

Abstract: The title compound, C20H18F6N2, a Schiff base, was synthesized by the reaction of 1,4‐diaminobutane and 4‐(trifluoromethyl)benzaldehyde in chloroform solution and was crystallized from a mixture of ethanol and dichloromethane (1:1). It lies across a crystallographic inversion centre. The crystal packing is stabilized by C—H...F hydrogen bonds and π–π interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…For general background, see: Kawski et al (2007). For related structures, see: Reffner & McCrone (1959); Dattagupta & Saha (1973); Herbstein et al (1984); Mahadevan et al (1982); Habibi et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For general background, see: Kawski et al (2007). For related structures, see: Reffner & McCrone (1959); Dattagupta & Saha (1973); Herbstein et al (1984); Mahadevan et al (1982); Habibi et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…Although the unit-cell parameters of DMABA have been reported (Reffner & McCrone, 1959), to our knowledge there is no report on the crystal structure of DMABA. The crystal structures of DMABA hydrobromide (Dattagupta & Saha, 1973), a 1:1 complex in which DMABA acts as a guest molecule in channels (Herbstein et al, 1984), a tin complex in which DMABA serves as a ligand coordinating through its O atom (Mahadevan et al, 1982), and of a 1:1 cocrystal of DMABA and 6-phenyl-1,3,5-triazine-2,4-diamine (Habibi et al, 2007) have been reported. We report here the crystal structure of the title compound.…”
Section: -(Dimethylamino)benzaldehydementioning
confidence: 99%
“…The crystal structures of 2,4-diamino-6-methyl-1,3,5-triazine (Aoki et al, 1994), 2,4-diamino-6-methyl-1,3,5-triazin-1-ium trifluoroacetate (Perpé tuo & Janczak, 2007), 4-(dimethylamino)benzaldehyde and 6-phenyl-1,3,5-triazine-2,4-diamine (Habibi et al, 2007), acetoguanaminium chloride-acetoguanamine (Portalone & Colapietro, 2007), acetoguanaminium N,N-dimethylformamide solvate (Portalone, 2008), 2,4-diamino-6-methyl-1,3,5-triazine methanol solvate (Kaczmarek et al, 2008) and 2,4-diamino-6-methyl-1,3,5-triazine ethanol solvate (Xiao, 2008) have been reported. Salts and cocrystals involving 2,4-diamino-6-methyl-1,3,5-triazine and various aliphatic dicarboxylic acids have been reported (Delori et al, 2008).…”
Section: Commentmentioning
confidence: 99%
“…For related literature, see: Bernstein et al (1995); Bork et al (2003); Chen et al (2001); Cox (1994); Desiraju (1989); Diaz-Ortiz et al (2004); Etter (1990); Habibi et al (2007); Janczak & Perpé tuo (2004); Lynch & Jones (2004); MacDonald & Whitesides (1994); Martindale (1996); Raj et al (2003); Sheshmani et al (2006); Perpé tuo & Janczak (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…The adducts of carboxylic acids with 2-aminoheterocylic ring system forms a graph-set motif of R 2 2 (8) (Lynch & Jones, 2004). The crystal structure of 2,4-diamino-6-phenyl-1,3,5-triazine (Diaz-Ortiz et al, 2004), Melaminium maleate monohydrate (Janczak et al, 2004), 2,4-diamino-6-methyl-1,3,5-triazin-1-ium trifluoroacetate (Perpétuo & Janczak, 2007), 4-(dimethylamino)-benzaldehyde and 6-phenyl-1,3,5-triazine-2,4-diamine (Habibi et al, 2007) and 2,6-diamino-4-phenyltriazinium chloride monohydrate (Sheshmani et al, 2006) have also been reported in the literature. The crystal structure of sorbic acid (Cox, 1994) is known.…”
Section: S1 Commentmentioning
confidence: 99%